Enhanced coupling of electronic and photonic states in a microcavity-quantum dot system - DONEGAN, JOHN; RAKOVICH, YURY (My University, 2005)
Spherical microcavities consisting of a dielectric material show unique optical characteristics as resonators in combination with semiconductor nanoparticles. A high quality factor results in a very narrow bandwidth of the resonant modes (whispering-gallery modes) inside the microcavity. The polystyrene microspheres are coated with one monolayer of CdTe nanocrystals which offer a high photostability and a high quantum yield at room temperature. Due to strong confinement of the electrons in all three dimensions, excitation from the quantum dots is highly size-dependent and tuneable over almost the whole visible spectrum. The deposition of the nanocrystals on the sphere surface allows efficient coupling of the light of the CdTe quantum dots into the microcavity. Photoluminescence and Raman spectra were taken with a Renishaw Raman system. The setup is equipped with an Ar+-laser and a HeNe-laser to excite the nanocrystals. Raman measurements show a series of very sharp resonant peaks instead of a continuous spectrum. Strong interaction between the electronic states of the nanocrystals and the resonant modes in the microsphere causes a considerable enhancement of the Raman scattering and luminescence from the CdTe quantum dots in Stokes and anti-Stokes region. Furthermore, a linear blue shift of the resonances in the photoluminescence spectrum was observed during continuous excitation for 18 minutes with a HeNe laser.
Opto-Ireland 2005: Optoelectronics, Photonic Devices, and Optical Networks
PUBLISHED
Dublin, Ireland
Keywords: Raman scattering; Photoluminescence; spherical microcavity; microsphere; nanocrystals; quantum dots